Operasi Plasik Dalam Perspekif Fiqh Kontemporer - Anisa Anisa Tanjung; Zelva Zelva Zahrani; Rohani Rohani Mustaqim; Ali Khaidir Ali; Qodri Muskalana Qodri (Yayasan Dar Arrisyah Indonesia, 2025)
Plastic surgery represents a significant advancement in the medical field, sparking diverse perspectives in contemporary Islamic jurisprudence. This phenomenon encompasses not only health-related concerns but also ethical, legal, and religious dimensions. In Islamic legal discourse, altering the physical form created by Allah SWT is a sensitive issue, especially when done solely for aesthetic purposes without medical necessity. This article aims to evaluate contemporary scholars’ views on plastic surgery by examining the various types of procedures (hajiyah and tahsiniyah), their Islamic legal basis, and the conditions under which they may be permitted. The research employs a descriptive qualitative approach through a literature review of scholarly opinions and contemporary sources. The findings indicate that plastic surgery is permissible in Islam if intended to restore bodily function or correct deformities caused by accidents, congenital conditions, or other medical needs. However, when carried out purely to alter Allah’s creation for personal satisfaction, such acts are considered a form of tasyabbuh (imitation) and are therefore prohibited. Consequently, contemporary Islamic jurisprudence allows for a degree of flexibility regarding plastic surgery, provided it aligns with the principles of maqāṣid al-sharī‘ah and is approached with caution.